2023
DOI: 10.3390/ma16165705
|View full text |Cite
|
Sign up to set email alerts
|

Study of Effective Stress Intensity Factor through the CJP Model Using Full-Field Experimental Data

Alonso Camacho-Reyes,
Jose Manuel Vasco-Olmo,
Giancarlo Luis Gómez Gonzales
et al.

Abstract: In this work, the Christopher–James–Patterson crack tip field model is used to infer and assess the effective stress intensity factor ranges measured from thermoelastic and digital image correlation data. The effective stress intensity factor range obtained via the Christopher–James–Patterson model, which provides an effective rationalization of fatigue crack growth rates, is separated into two components representing the elastic and retardation components to assess shielding phenomena on growing fatigue crack… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…to meters. [1][2][3] Particularly, in the study of fatigue crack propagation, [4][5][6][7][8] DIC has found successful applications for investigating material fracture mechanisms, significantly expanding its use over the past decades. However, despite the robust performance shown by this method, characterizing the crack tip field, where significant strain variations occur over a short distance, may present challenges for the DIC algorithm.…”
mentioning
confidence: 99%
“…to meters. [1][2][3] Particularly, in the study of fatigue crack propagation, [4][5][6][7][8] DIC has found successful applications for investigating material fracture mechanisms, significantly expanding its use over the past decades. However, despite the robust performance shown by this method, characterizing the crack tip field, where significant strain variations occur over a short distance, may present challenges for the DIC algorithm.…”
mentioning
confidence: 99%